RI 6258 Sulfatization Of Manganiferous Carbonate Slates In A Fluidized Bed Reactor - Charles Prasky (The National Institute for Occupational Safety and Health (NIOSH), 1963)
This report describes fluidized bed techniques employed by the Bureau of Mines at Minneapolis to differentially sulfatize the manganese in two samples of low-grade manganiferous ferruginous carbonate slates from the Cuyuna Range district, Minn. Suitable mechanics of operation were established. A space rate of 1.25 to 1.5 fps, a retention time of 3 to 3.5 hours, a temperature of 700° C, and a 10 percent sulfur dioxide gas in air were adequate for sulfatizing the slates by fluidization. Under these conditions the overflow product removal rate from the 4-inch-diameter reactor was 4 to 5 pounds per hour. The sulfur dioxide was used more efficiently in the two-stage treatment than in the single-stage treatment. However, approximately 80 percent of the manganese was converted to sulfate by either treatment.